2021
DOI: 10.1007/s10956-021-09924-1
|View full text |Cite
|
Sign up to set email alerts
|

A Learning Experience in Inquiry-Based Physics with Immersive Virtual Reality: Student Perceptions and an Interaction Effect Between Conceptual Gains and Attitudinal Profiles

Abstract: The integration of immersive virtual reality (VR) in authentic science classrooms can result in a totally new learning experience for the students. However, the effect of such a learning experience on students' conceptual learning gains and their perceptions of the experience, while considering students' pre-existing science-and digital technologies-related attitudinal profiles, has not been explored to date. In this study, we have enacted a 90-min technology-enhanced inquiry-based intervention with high-schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 91 publications
2
21
0
1
Order By: Relevance
“…Virtual reality (VR) is rapidly developing as a future interactive medium with various advantages in the educational field (Fussell & Truong, 2021;Tsivitanidou et al, 2021). Aligning with the organizational change of Facebook to Meta regarding its investment in Metaverse (Kraus et al, 2022), VR is reportedly becoming more popular in integrating classroom learning.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR) is rapidly developing as a future interactive medium with various advantages in the educational field (Fussell & Truong, 2021;Tsivitanidou et al, 2021). Aligning with the organizational change of Facebook to Meta regarding its investment in Metaverse (Kraus et al, 2022), VR is reportedly becoming more popular in integrating classroom learning.…”
Section: Introductionmentioning
confidence: 99%
“…The IMMS instrument, used to measure motivational factors, is largely based on the perceptions that students had during the experimental process. With this in mind, there is a possibility that students may not answer the questions seriously, or even answer inaccurately, because they may not be fully aware of what affects their motivation [42]. Thus, it is important that the items used to measure motivational factors are clear and easy to understand, considering that such questions should address aspects related to the learning content (information), the environment (presentation, presence), as well as how the learner engages (interactivity, agency) with the learning tool [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing body of research that looks at inquiry and problem‐solving processes using video recordings, eye‐tracking data or other spatial data sources to create the process‐based log data of participants working with tools in physical open‐ended learning environments (Bumbacher et al, 2018; Davis et al, 2017; Radu & Schneider, 2019). Similarly, recent work examined the use of immersive virtual realities (VR) for science inquiry, which can produce rich data streams from students' interactions with the VR environment (Tsivitanidou et al, 2021). Future studies should examine to what extent the approaches and techniques that we have identified in the present study could be applied to log data generated in different platforms.…”
Section: Discussionmentioning
confidence: 99%